TEKNIK MEMBACA SQ3R DALAM MEMBACA KRITIS UNTUK PENGUATAN PENDIDIKAN KARAKTER DI PERGURUAN TINGGI - Purwati Zisca Diana (CARAKA, 2014)
Reading skills are still considered very important. This is due to the fact that reading skills do not only play a role in improving language skills but further provide benefits to increase the ability of students in other subjects. Reading skills is not currently focused on efforts to form young people who love to read. This is evidenced by the low interest on student reading. In this paper, talked about the integration of character education in learning to read by using reading techniques SQ3R in critical reading.